Nation Branding and How It Is Related to Foreign Direct Investment Inflows - Lahrech, Abdelmounaim; Alabdulwahab, Sami Zaki; Bouayach, Safaâ (International Journal of Economics and Financial Issues, 2020)
This study examines the existence of a correlation between the Brand Image of a country and its FDI Inflows. Furthermore, does the Brand Image of a country have a positive impact on its FDI inflows? To proceed to the object of the study, we use a panel model regression that applies to the ten best Nation Branding Index (NBI) countries between 2008 and 2014. The result illustrates a strong positive correlation between nation branding and FDI inflow, indicating that nation branding plays a significant role in attracting business to the country. Moreover, countries that exhibit high nation branding have a tendency to have significant increases in FDI inflows. Keywords: Nation Branding Index, Foreign Direct Investment, Trade Openness, Growth Real GDP, Political Stability, Control of Corruption, Panel Estimation JEL Classifications: F3, M2, O19 DOI: https://doi.org/10.32479/ijefi.9345